2010
DOI: 10.1007/s12562-010-0280-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunological effects of glucan and Lactobacillus rhamnosus GG, a probiotic bacterium, on Nile tilapia Oreochromis niloticus intestine with oral Aeromonas challenges

Abstract: The present study histologically examined the effects of glucan-containing and Lactobacillus rhamnosus GG (LGG)-containing diets on intestinal damages inflicted on Nile tilapia by Aeromonas challenges. Tilapia were fed control, glucan, and LGG diets for 2 weeks and were subsequently challenged with Aeromonas. The intestines were then histologically examined at 1, 7, 14, and 21 days post-infection. Mortality following the challenge was lower for the fish fed the glucan and LGG diets. The intestines of these gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 26 publications
(29 reference statements)
4
35
0
1
Order By: Relevance
“…According to Soto [28] it is proven that bacteria are the cause of epithelial hyperplasia in gills, splenomegaly, renomegaly and necrosis in internal organs, mainly in spleen, heart, liver, kidney, brain and musculature. For example Yardimci, et al [29][30][31] indicate that species Aeromonas hydrophila is associated with hemorrhages in gills and skin, weakness and anorexia, as well as vision loss by breaking' orbital eyes, the above agrees with those reported by Clavijo et al [32], who reported that the presence of genus Edwardsiella sp., causes septicemia in internal and external organs, including kidney, liver and spleen, skin, rectum, fins, abdominal inflammation, and opaque eyes. Some pathogens are transmitted horizontally as indicated by Mauel et al [33], who pointed out that bacteria use water as a precursor vehicle, causing fish-to-fish outbreaks by direct contact.…”
Section: Discussionsupporting
confidence: 78%
“…According to Soto [28] it is proven that bacteria are the cause of epithelial hyperplasia in gills, splenomegaly, renomegaly and necrosis in internal organs, mainly in spleen, heart, liver, kidney, brain and musculature. For example Yardimci, et al [29][30][31] indicate that species Aeromonas hydrophila is associated with hemorrhages in gills and skin, weakness and anorexia, as well as vision loss by breaking' orbital eyes, the above agrees with those reported by Clavijo et al [32], who reported that the presence of genus Edwardsiella sp., causes septicemia in internal and external organs, including kidney, liver and spleen, skin, rectum, fins, abdominal inflammation, and opaque eyes. Some pathogens are transmitted horizontally as indicated by Mauel et al [33], who pointed out that bacteria use water as a precursor vehicle, causing fish-to-fish outbreaks by direct contact.…”
Section: Discussionsupporting
confidence: 78%
“…In our previous study, the use of a combination of dietary beta-glucans (b-G) and mannan oligosaccharides (MOS) resulted in better performance in terms of growth rate, intestinal morphology, immune response and disease resistance, than the use of B. amyloliquefaciens tilapia under the same circumstances [23,104]. Similarly, Ngamkala et al [105] reported that glucan elicited better immunostimulation and resistance against A. hydrophila in tilapia than the probiotic L. rhamnosus. These finding might be attributable to higher numbers of double-staining mucous cells and faster increases in inflammatory cell infiltration that began after 1 d of infection and continued thereafter.…”
Section: Discussionmentioning
confidence: 96%
“…Before and after challenge, goblet cells in the control fish were mainly filled with an acid type mucin. In the β‐glucan fed group, after challenge, the AB‐PAS double‐stained cell type, dominated, which contains acid and neutral mucins (Ngamkala et al., ). The authors concluded that the cell type shift appeared to be signalled by a combination of the Aeromonas challenge and effects due to the feeding of β‐glucan.…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown in Asian catfish ( Clarias batrachus ; Kumari & Sahoo, ,b), common carp ( Cyprinus carpio ; Selvaraj et al., ), catla ( Catla catla ; Kamilya, Maiti, Joardar, & Mal, ), nile tilapia ( Oreochromis niloticus ; El‐Boshy, El‐Ashram, Abdelhamid, & Gadalla, ), rainbow trout (Douxfils, Fierro‐Castro, Mandiki, Emile, & Tort, ), roho ( Labio rohita ; Misra, Das, Mukherjee, & Pattnaik, ; Sahoo & Mukherjee, ) and zebrafish ( Danio rerio ; Rodriguez, Chamorro, Novoa, & Figueras, ) challenged with Aeromonas hydrophila , as well as Nile tilapia ( Oreochromis niloticus ) infected with Aeromonas spp. (Ngamkala et al., ), carp (Falco et al., ) and rainbow trout ( Oncorhynchus mykiss ; Ji et al., ) infected with Aeromonas salmonicida , large yellow croaker ( Pseudosciaena crocae ) infected with Vibrio harveyi (Ai et al., ), rohu (Sahoo & Mukherjee, ) and zebrafish (Udayangani et al., ) infected with Edwardsiella tarda , nile tilapia infected with Streptococcus agalactiae (Pilarski, Ferreira de Oliveira, Darpossolo de Souza, & Zanuzzo, ) and Channel catfish ( Ictalurus punctatus ) infected with Edwarsiella ictaluri (Welker, Lim, Yildirim‐Aksoy, & Klesius, ; Welker, Lim, Yildirim‐Aksoy, Shelby, & Klesius, ). In most of these studies, bacteria were injected into the body cavity of the fish (Ai et al., ; Dale, Gutenberger, & Rohovec, ; El‐Boshy et al., ; Falco et al., ; Kamilya et al., ; Kumari & Sahoo, ,b; Rodriguez et al., ; Sahoo & Mukherjee, , ; Selvaraj et al., ).…”
Section: Introductionmentioning
confidence: 99%